2012
DOI: 10.1096/fj.12-210989
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal air pollution exposure induces neuroinflammation and predisposes offspring to weight gain in adulthood in a sex‐specific manner

Abstract: Emerging evidence suggests environmental chemical exposures during critical windows of development may contribute to the escalating prevalence of obesity. We tested the hypothesis that prenatal air pollution exposure would predispose the offspring to weight gain in adulthood. Pregnant mice were exposed to filtered air (FA) or diesel exhaust (DE) on embryonic days (E) 9-17. Prenatal DE induced a significant fetal brain cytokine response at E18 (46-390% over FA). As adults, offspring were fed either a low-fat di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(195 citation statements)
references
References 53 publications
9
183
1
2
Order By: Relevance
“…Besides that, we observed decreased plasma levels of glutathione and folate only in adult male [27], corroborating that female and male offspring responded differently to methyl donor deficiency in utero. Indeed, studies on epigenetic mechanisms have shown that males may be more susceptible in adulthood due to epigenetic marks generated during embryonic period [36,37]. The offspring's care, usually associated to females, is suggested as a selective pressure agent [38].…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, we observed decreased plasma levels of glutathione and folate only in adult male [27], corroborating that female and male offspring responded differently to methyl donor deficiency in utero. Indeed, studies on epigenetic mechanisms have shown that males may be more susceptible in adulthood due to epigenetic marks generated during embryonic period [36,37]. The offspring's care, usually associated to females, is suggested as a selective pressure agent [38].…”
Section: Discussionmentioning
confidence: 99%
“…La dégradation de la qualité de l'alimentation dans les pays déve-loppé et la contamination de notre environnement par des perturbateurs endocriniens sont les facteurs les plus souvent incriminés pour comprendre l'épidémie actuelle d'obésité et de maladies métaboliques. Cependant, l'exposition chronique à la pollution atmosphérique pourrait aussi jouer un rôle, comme le suggère en particulier une étude chez la souris qui montre que l'exposition foetale à des gaz d'échappement diesel augmente la réponse post-natale à un régime obésogène, avec des effets qui varient selon le sexe de l'individu (Bolton et al 2012, Bolton et al 2013). …”
Section: Discussion Et Conclusionunclassified
“…Aux concentrations d'exposition les plus élevées, l'expression génique placentaire de plusieurs cytokines proinflammatoires (interleukines IL-4, IL-5, IL-6, IL-12a et b) est très largement augmentée (Fujimoto et al 2005). L'exposition in utero à des concentrations élevées de DE induit aussi une augmentation marquée de l'expression d'interleukines (IL-1b, IL-6, IL-10) et de chimiokines (chemokine ligand 2 et fractalkine) dans le cerveau des foetus à terme (Bolton et al 2012 (Valentino et al 2016).…”
Section: Exposition Par Inhalationunclassified
“…Epidemiologic studies evidence that diabetic individuals are adversely affected by air pollution exposure [9] Obesity is the primary cause underlying the development of insulin resistance and type 2 diabetes [10] and is associated with chronically elevated plasma levels of IL-6 [11]. Studies in experimental rat models have shown that air pollution agg ravates inflammation and insulin resistance especially in obese animals [12].…”
Section: Introductionmentioning
confidence: 99%